Differences in Characteristics of Farmers who Adopt and Who Do not Adopt a Cattle Business Insurance Program - Ica Azisah Riana; Syahdar Baba; Sitti Nurani Sirajuddin (Hasanuddin Journal of Animal Science (HAJAS), 2019)
One government program through the Ministry of Agriculture of the Republic of Indonesia is insurance for cattle business as a manifestation of the government's partisanship in an effort to protect cattle farmers from the risk of death and loss of cattle.  To support the program, Gowa Regency has implemented a cattle business insurance program.  Farmers are a very influential factor in the adoption of cattle business insurance programs that have different characteristics to adopt so as to minimize the risk of their livestock business.This study aims to determine the differences in characteristics of farmers who adopt and who do not adopt a cattle business insurance program.  This research was conducted in Bungaya District, Gowa Regency from February to March 2019. The method used is descriptive research using 98 farmers as a sample consisting of 63 people who adopted and 35 people who did not adopt, data collected through interviews and analyzed descriptively statistically.  The results showed that differences in the characteristics of farmers who adopted and did not adopt a cattle business insurance program consisting of:(a) the age of farmers is mostly 38 to 54 years with those adopting 35 people and those who do not adopt 16 people; (b) most of them are male, where 51 farmers adopt and 28 farmers who do not adopt; (c) the last level of education of the farmer is mostly elementary school/equivalent who adopted as many as 25 people and those who did not adopt 14 people; (d) the total number of family members of farmers is 4 to 6 in which 29 people adopt and 22 people do not adopt; (e) the scale of the business of most 1 to 7 cattle owned by farmers as many as 54 people who adopted and 32 people who did not adopt; and (f) the experience of raising is mostly in the range of 10 to 23 years where those who adopt as many as 40 people and those who do not adopt 24 people.